2013
DOI: 10.11648/j.sjph.20130104.12
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude and Factors Associated with Malnutrition in Children 6-59 Months of Age in Pastoral Community of Dollo Ado District, Somali Region, Ethiopia

Abstract: Background: Malnutrition at the early stages of life can lower child resistance to infections, increase child morbidity and mortality, and decrease mental development and cognitive achievement. Adequate nutrition is the keystone of survival, health and development not only of current generations but also of the ones to come. Child malnutrition is a major public health problem in Ethiopia. Objectives: To assess the magnitude and factors associated with malnutrition of children 6 to 59 months of age in Dollo Ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

76
167
13
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 186 publications
(260 citation statements)
references
References 15 publications
76
167
13
4
Order By: Relevance
“…The result is similar to studies conducted in Somali region [12], Ethiopia, Oromia region West Ethiopia [14], and Gambit, Ethiopia [9]. Similarly, other studies conducted in Iran [6], Nigeria [7], north Sudan [10] and Zimbabwe [11] argued that low family income was the risk factor for under five acute malnutrition.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The result is similar to studies conducted in Somali region [12], Ethiopia, Oromia region West Ethiopia [14], and Gambit, Ethiopia [9]. Similarly, other studies conducted in Iran [6], Nigeria [7], north Sudan [10] and Zimbabwe [11] argued that low family income was the risk factor for under five acute malnutrition.…”
Section: Discussionsupporting
confidence: 86%
“…Children whose mothers are illiterate were 4 fold at risk to have severe acute malnutrition as compared to those children have literate mothers. Similar findings were revealed at studies done in Shashogo Woreda, Southern Ethiopia [22], Gonder, Ethiopia [17], Oromia region, West Ethiopia [14], Somali Region, Ethiopia [12], in Ghana [24], Gambia and Nigeria [18], Bangladesh [25] and Granada, Nicaragua [26]. This could be due to illiterate mothers have less perception about the nutritional need of their children and most of them have poor socio-economic status.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…So, this could be again a concern for further researches to know the anemia status of those children and others as cow's milk consumption by infants less than 12 months of age was common practice there though it was shown that cow's milk consumption had protective effect against being underweight. Another determinant factor of underweight in the current study was the main source of water to the household though association was not found in other studies of regions of the country (23,28) and developing countries (15,16); but, in this current study those children of food insecure households who were used to river water as main source were 2.75 times at higher risk to be underweight compared to those children of who were used to pipe (hand pump) as main source of water. And this might be as reasons of poor households were more likely to obtain water from unsafe sources.…”
Section: Underweightcontrasting
confidence: 86%
“…And this was supported by different studies (14,26) but in contradiction with the studies (15,23). As a final point, children of food insecure households who were used to Protected and unprotected well/Spring as main source of water were 2.95 and 3.54 times at higher risk to be wasted respectively; compared to those children of who were used to pipe (hand pump) as main source of water.…”
Section: Wastingmentioning
confidence: 90%